Several Leading Members of the Uprising Serving Life Sentence will be Retried by a Military Tribunal - Héderváry, Claire de (1960)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Strong reason to suspect that their life sentences are being changed to death sentences.